Identification of F3H, Major Secondary Metabolite-Related Gene That Confers Resistance against Whitebacked Planthopper through QTL Mapping in Rice - Eun-Gyeong Kim; Sopheap Yun; Jae-Ryoung Park; Kyung-Min Kim (Plants, 2021)
Whitebacked planthopper (WBPH) is a pest that causes serious damage to rice in Asian countries with a mild climate. WBPH causes severely rice yield losses and grain poor quality each year so needs biological control. Plants resist biotic and abiotic stress using expressing variety genes, such as kinase, phytohormones, transcription factors, and especially secondary metabolites. In this research, quantitative trait locus (QTL) mapping was performed by assigning the WBPH resistance score in the Cheongcheong/Nagdong doubled haploid (CNDH) line in 2018 and 2019. The RM280-RM6909 on chromosome 4 was detected as a duplicate in 2018, 2019, and derived from Cheongcheong. This region includes cell function, kinase, signaling, transcription factors, and secondary metabolites that protect plants from the stress of WBPH. The RM280-RM6909 on chromosome 4 contains candidate genes that are similar to the flavanone 3-hydroxylase (F3H) of rice. The F3H are homologous genes, which play an important role in biosynthesis defending against biotic stress in plants. After WBPH inoculation, the relative expression level of F3H was higher in resistant line than in a susceptible line. The newly identified WBPH resistance gene F3H by QTL mapping can be used for the breeding of rice cultivars that are resistant against WBPH.